CT FINDINGS OF THREE GIANT MEDIASTINAL TUMORS IN YOUNG AGE - Arifah, Arifah; Erawati, Dini Rachma (Department of Radiology, Medical Faculty, University of Brawijaya, 2022)
Background : Mediastinal teratoma and other mediastinal tumors are very challenging to be distinguished from other mediastinal tumors. Mediastinal tumors can be optimally evaluated with computed tomography (CT). In this paper we present three young male patients with similar symptom of chronic chest pain and chronic cough. Materials and Methods: Conducting a literature review and medical records. Results : All patients in this case are young age male, below two decades. All chest CT shows giant mass, but they have different enhancing pattern, different amount of solid, cystic, calcification component. To make correct diagnosis of the mediastinal mass is important because of treatment planning difference, surgery or chemoteraphy. The first case shows benign teratoma with characteristic of heterogenous mass with large amount of fat, with presence of solid and calcification component. The second case shows malignant germ cell tumor with feature of heterogenous mass with predominantly solid component and small amount of fat. It also shows metastatic process in lung and bone. The third case shows Hodgkin lymphoma with slight enhanced mass that narrowed pulmonary artery and caused pericardial effusion. Conclusion: Various features of mediatinal tumors can be distinguished with CT modality.